Early introduction of simulation in the medical curriculum: the MedInTo perspective - Lembo, David; Abate Daga, Federico; Calì, Corrado; Garbossa, Diego; Manfredi, Matteo; Odetto, Lorenzo; Ostacoli, Luca; Paccotti, Piero; Raimondo, Stefania; Reimondo, Giuseppe; Sciascia, Savino (Frontiers in Medicine, 2024)
Despite the increasing body of evidence supporting the use of simulation in medicine, a question remains: when should we introduce it into the medical school's curriculum? We present the experience and future perspectives of the MD program in Medicine and Surgery of University of Turin-MedInTo. Since its launch, MedInTo has been dedicated to integrating innovative teaching approaches at the early stages into the medical curriculum. Herewith, we describe a case-based approach for our activities, which includes the utilization of simulation for emergency medical care training for students and the integration of virtual and augmented reality technology. Dedicated surgical training activities using virtual-augmented reality and life-like simulator for students are also described.